Le sang, notion politique et régulateur social sous l’Ancien Régime. Pour une histoire longue de la race - Jean-Frédéric Schaub (Clio@Themis)
Historians who argue that the racial question only takes shape in modern times usually assume that the evocation of blood was just a metaphor before the blooming of so-called scientific racism. Before that, blood was a way to express the importance of the lineage identity, through the image of the blood that flows from generation to generation. This article, based on both normative and literary sources, intends to show, on the contrary, that from the end of the Middle Ages, the real blood is instituted as the bearer of the qualities and the dignity of the people in the social system.